The potential effect of Moringa oleifera leaves extract on vascular endothelial growth factor expression in Wistar rat oral cancer cells - Dwicha Rahma Nuriska Hartono; Theresia Indah Budhy Sulisetyawati; Edhi Jularso (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Cancer is a disease characterized by abnormal and uncontrolled growth of tissue cells. In Indonesia, cancer ranks as the fifth largest cause of mortality, while it is the second largest worldwide. Cancer affected by angiogenesis, the process of forming new blood vessels to provide the nutrient and oxygen necessary for tumor growth. Vascular endothelial growth factor (VEGF) represents a pro-angiogenic factor. Moringa oleifera leaf extract can be used as an anticancer agent by reducing the expression of VEGF. Purpose: The study aimed to prove that Moringa oleifera leaf extract can reduce VEGF expression in benzopyrene-induced oral cancer cells of Wistar rats. Methods: This was an experimental laboratory research with posttest-only control group design. All experimental subjects presented symptoms of cancer following induction with 8 mg/KgBW of benzopyrene. The sample consisted of 28 Wistar rats, divided into four groups, namely; a control group (K) whose members were administered with only aquadest and three treatment groups (P) treated with Moringa oleifera leaves extract at percentages of 3.125% (P1), 4.6875% (P2) and 6.25% (P3) respectively. Observation of VEGF expression was undertaken by means of immunohistochemical staining. Results: A decrease in VEGF expression occurred in all treatment groups when compared with the control group. A significant difference existed between the control group (K) and the treatment group (P1), while there were no significant differences between the treatment groups (P1, P2 and P3). Conclusion: Moringa oleifera leaf extract with a percentage of 3.125% proved most effective at reducing VEGF expression in oral cancer cells in Wistar rats.